The impact of CSR disclosure, audit committees, independent commissioners, and managerial ownership on corporate value: An empirical study of basic materials sector companies listed on the Indonesian stock exchange - Dewi, Friska Nabila; Soemantri, Roebiandini (Universitas Padjadjaran, 2025)
Negative sentiments stemming from declining aluminum exports, coal price fluctuations, a global economic slowdown, and environmental pressures influence investors' perceptions of investing in the raw materials sector. CSR disclosure and implementing Good Corporate Governance principles through audit committees, independent commissioners, and managerial ownership are vital strategies for enhancing investor confidence and long-term corporate value. This study investigates the effect of CSR disclosure and corporate governance attributes on corporate value, with Return on Assets as the control variable. It utilizes secondary data from annual and sustainability reports, focusing on companies in the basic materials sector listed on the Indonesia Stock Exchange from 2020 to 2023. Quantitative methods are employed, with panel data regression analysis. The results indicate that, partially, CSR disclosure has a negative and significant impact on corporate value, whereas the proportion of the audit committee exhibits a positive and significant effect. The frequency of audit committee meetings and the proportion of independent commissioners do not demonstrate a significant impact. Audit committee competence positively and significantly influences corporate value, while managerial ownership adversely and significantly affects it. Collectively, these variables influence corporate value. These findings provide valuable insights for company management to enhance CSR and governance practices, thereby increasing the company's appeal to investors